Stability of cp-Ti and Ti-6Al-4V alloy for dental implants as a function of saliva pH - an electrochemical study - Barao, Valentim Adelino Ricardo [UNESP]; Mathew, Mathew T.; Assunção, Wirley Goncalves [UNESP]; Yuan, Judy Chia-Chun; Wimmer, Markus A.; Sukotjo, Cortino (Wiley-Blackwell, 2012)
Objectives To investigate the role of different levels of pH of artificial saliva under simulated oral environment on the corrosion behavior of commercially pure titanium (cp-Ti) and Ti-6Al-4V alloy. Special attention is given to understand the changes in corrosion kinetics and surface characterization of Ti by using electrochemical impedance spectroscopy (EIS). Materials and methods Fifty-four Ti disks (15-mm diameter, 2-mm thickness) were divided into six groups (n similar to=similar to 9) as a function of saliva pH (3, 6.5, and 9) and Ti type. Samples were mechanically polished using standard metallographic procedures. Standard electrochemical tests, such as open circuit potential, EIS, and potentiodynamic tests were conducted in a controlled environment. Data were evaluated by two-way ANOVA, Tukey multiple comparison test, and independent t-test (a similar to=similar to 0.05). Ti surfaces were examined using white-light-interferometry microscopy and scanning electron microscopy (SEM). Results Saliva pH level significantly affected the corrosion behavior of both Ti types. At low pH, acceleration of ions exchange between Ti and saliva, and reduction of resistance of Ti surface against corrosion were observed (P similar to<similar to 0.05). Corrosion rate was also significantly increased in acidic medium (P similar to<similar to 0.05). Similar corrosion behavior was observed for both Ti types. The white-light-interferometry images of Ti surfaces show higher surface changes at low pH level. SEM images do not show detectable changes. No pitting corrosion was observed for any group. Conclusions The pH level of artificial saliva influences the corrosion behavior of cp-Ti and Ti-6Al-4V alloy in that lower pH accelerates the corrosion rate and kinetics. The corrosion products may mitigate the survival rate of dental implants.
Keywords: artificial saliva; corrosion; electrochemistry; pH level; titanium